Isolation properties and failure mechanisms of vertical Pt / n-GaN SBDs. (November 2022) - Fregolent, M.; Boito, M.; Marcuzzi, A.; De Santi, C.; Chiocchetta, F.; Treidel, E. Bahat; Wolf, M.; Brunner, F.; Hilt, O.; Würfl, J.; Meneghesso, G.; Zanoni, E.; et al.
Abstract: This paper reports on the isolation properties and failure mechanism of n -type vertical Pt / n -GaN Schottky barrier diodes and the dependence on the drift layer doping concentration. The results indicate that (i) independently on doping density, the Schottky barrier height is lower than the theoretical expectation, and this limits the blocking properties of the junction; (ii) barrier lowering was associated to an injection mechanism that involves deep levels in the semiconductor layer, near the junction, favouring injection and tunneling of carriers. By performing a detailed analysis of the breakdown mechanism, we also demonstrated that (iii) the failure of the devices in reverse bias condition is related to a power-related mechanism associated to current flowing along the mesa edges. We thus conclude that (iv) a good edge termination and passivation of the surfaces is fundamental to exploit the full blocking capability of the semiconductor. Highlights: Pt/GaN Schottky barrier diodes present barrier height lower than the theoretical one. Failure of the devices can be ascribed to a power-related mechanism. The devices present strong electroluminescence spots, distributed on device area. Formation of the EL spots is correlated with the increase of the leakage current.